JISMONIY TARBIYA VA SPORT DARSLARIDA PEDAGOGIK TEXNOLOGIYALAR: ZAMONAVIY YONDASHUVLAR - Karimov, B.B. (SCIENCE and SOCIETY, 2025)
This article examines the application of modern pedagogical technologies in physical education and sports lessons, highlighting their key principles and significance. It presents methods for organizing effective classes using interactive techniques, information and communication technologies, and individualized approaches. These methods contribute not only to students' physical development but also to the enhancement of their intellectual and social skills.
Keywords: physical education; sports; pedagogical technologies; interactive methods; modern approaches; multimedia; differentiated approach